Integration of Carbon Nanotubes in Silicon Strip and Slot Waveguide Micro-Ring Resonators - Duran-Valdeiglesias, Elena; Zhang, Weiwei; Noury, Adrien; Alonso-Ramos, Carlos; Thi Hong Cam Hoang; Serna, Samuel; Le Roux, Xavier; Cassan, Eric; Izard, Nicolas; Sarti, Francesco; Torrini, Ughetta; Biccari, Francesco; et al. (IEEE Transactions on Nanotechnology, 2016)
Silicon photonics has emerged as a very promising technology platform for the implementation of high-performance, low-cost, ultra-compact circuits that can monolithically co-integrate electronic, opto-electronic and optic functionalities. However, Si neither has efficient light emission or detection in the telecom wavelength range, nor exhibits efficient electro-optic Pockels effect, hindering the implementation of integrated active devices like sources, detectors, or modulators. Current approaches relay on different materials to provide active functionalities in Si photonics, resulting in highly complex integration schemes that compromise cost-effectiveness. Semiconducting single-wall carbon nanotubes (SWNTs) are capable of emitting and detecting near-infrared light at room temperature and exhibit intrinsically fast electro-optic effects. They have also proven promising uses in micro-electronic devices, making them an ideal material to provide active functionalities in the Si photonic platform. In this work, we propose and experimentally validate the possible use of slot photonic waveguides to improve interaction between SWNTs and Si waveguide modes. Fabricated Si slot micro-ring shown an experimental ∼ 60% photo-luminescence improvement compared to previous demonstration based on Si strip waveguide resonators. These results prove the potential of Si slot waveguides for the implementation of efficient SWNT-based Si photonic devices.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Carbon nanotubes; light emission; ring resonator; silicon photonics